Journal of Geophysical Research: Oceans - Journal of Geophysical Research: Oceans (Wiley, 2026)
Journal of Geophysical Research: Oceans publishes new understanding of the ocean and its processes, including physical, biogeochemical, and sedimentary ocean processes and their interactions with other components of the Earth system.
FI 1.12
Q1
Keywords: Earth; Space & Environmental Sciences; Oceanography & Paleoceanography; Oceanografía; Paleoceanografía; Acuerdos transformativos; Transformative agreements; Procesos oceanográficos; Dinámica oceánica; Cambio oceánicos